Tissue MicroRNA profiles as diagnostic and prognostic biomarkers in patients with resectable pancreatic ductal adenocarcinoma and periampullary cancers - Calatayud, Dan (Biomark Res, 2017)
BACKGROUND: The aim of this study was to validate previously described diagnostic and prognostic microRNA expression profiles in tissue samples from patients with pancreatic cancer and other periampullary cancers. METHODS: Expression of 46 selected microRNAs was studied in formalin-fixed paraffin-embedded tissue from patients with resected pancreatic ductal adenocarcinoma (n = 165), ampullary cancer (n=59), duodenal cancer (n = 6), distal common bile duct cancer (n = 21), and gastric cancer (n = 20); chronic pancreatitis (n = 39); and normal pancreas (n = 35). The microRNAs were analyzed by PCR using the Fluidigm platform. RESULTS: Twenty-two microRNAs were significantly differently expressed in patients with pancreatic cancer when compared to healthy controls and chronic pancreatitis patients; 17 miRNAs were upregulated (miR-21-5p, −23a-3p, −31-5p, −34c-5p, −93-3p, −135b-3p, −155-5p, −186-5p, −196b-5p, −203, −205-5p, −210, −222-3p, −451, −492, −614, and miR-622) and 5 were downregulated (miR-122-5p, −130b-3p, −216b, −217, and miR-375). MicroRNAs were grouped into diagnostic indices of varying complexity. Ten microRNAs associated with prognosis were identified (let-7 g, miR-29a-5p, −34a-5p, −125a-3p, −146a-5p, −187, −205-5p, −212-3p, −222-5p, and miR-450b-5p). Prognostic indices based on differences in expression of 2 different microRNAs were constructed for pancreatic and ampullary cancer combined and separately (30, 5, and 21 indices). CONCLUSION: The study confirms that pancreatic cancer tissue has a microRNA expression profile that is different from that of other periampullary cancers, chronic pancreatitis, and normal pancreas. We identified prognostic microRNAs and microRNA indices that were associated with shorter overall survival in patients with radically resected pancreatic cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40364-017-0087-6) contains supplementary material, which is available to authorized users.